ALTERASI HIDROTERMAL ENDAPAN SINABAR DAERAH BUKIT TEMBAGA, IHA – LUHU, PULAU SERAM, MALUKU : HYDROTHERMAL ALTERATION OF CINNABAR DEPOSIT IN TEMBAGA HILL, IHA – LUHU - SERAM ISLAND, MALUKU - Herfien Samalehu; Arifudin Idrus; Nugroho Imam Setiawan (Buletin Sumber Daya Geologi, 2022)
Iha – Luhu area is located in the western part of Seram Island, which is about 59.2 km from city of Piru. Geographically, it is located at 128o0’35” to 128o2’42”East Longitude and 3o20’40” s.d 3o22’05”South Latitude and is included in Huamual sub-district, West Seram Regency, Maluku. Stratigraphy of Iha – Luhu is composed of metapelitic rock and low grade metamorphic lithologies, namely meta quartz – muscovite sandstone units and quartz – muscovite phyllite unit and is unconformaby covered by alluvial deposits. Research area consists of three hydrothermal alteration zones which are mentioned as illite±kaolinite alteration zone, illite±chlorite alteration zone and Illit±smectite±kaolinite alteration zone. Illite±kaolinite alteration zone is characterized by assemblage of clay minerals, presumably illite and kaolinite. This alteration is associated with quartz-muscovite meta-siltstone and dominant occurred to quartz-muscovite meta-sandstone. Intensity of alteration is moderate to strong altered which mainly describing percentage of alteration mineral presence more than 75%. Based on assemblage of kaolinite and illite alteration minerals thus illite±kaolinite alteration zone was formed at temperatures <220o-300o C. Illite±chlorite alteration zone is associated with fracture-related mineralization and disseminated enrichment of cinnabar ore deposits where alteration pattern is a pervasive alteration show. This zone is characterized by presence of mica (illite) clay mineral and chlorite and quartz as well. Illite±chlorite alteration is more dominantly associated with quartz-muscovite phyllite and quartz-muscovite meta-siltstone and spread over in the middle of Bukit Tembaga. Formation Temperature of this alteration zone is estimated at 250o – 300o C. Illite±smectite±kaolinite alteration zone spread widely on top of Bukit Tembaga to lowlands and reaching area of ​​> 9.6 Km2. This alteration covers illite ± chlorite and illite ± kaolinite alterations with pervasive alteration pattern and strong altered alteration. Clay in this zone occurred due to alteration of muscovite/sericite and plagioclase minerals. Presence of smectite in this alteration zone reflects vertical depth that is relatively far from ore zone or at top of formation with temperature tend to be lower than illite and kaolinite minerals. Formation temperature of this alteration zone is estimated at 220o-300o C.